A noncovalently connected metal–organic framework assembled from a Ni(iii)-supported polyoxometalate–imidazolate hybrid. Issue 13 (14th February 2017) - Jiao, Yan-Qing; Li, Meng-Ting; Qin, Chao; Su, Zhong-Min
Abstract : The first mixed-valence nickel-supported polyoxometalate-based metal–organic framework constructed via noncovalent interactions has been synthesized, exhibiting a hexagonal array of 1D large channels along the crystallographic c axis with a diameter of 18.83 Å. Abstract : The first mixed-valence nickel-supported polyoxometalate-based metal–organic framework, (H2 mim)[Ni III (Hmim)4 ][SiW11 Ni II O37 (OH)2 (Hmim)]·3H2 O (1 ) (Hmim = 2-methylimidazole), has been synthesized using a steam-assisted conversion method, and is constructed from noncovalent interactions (hydrogen bonds and π⋯π stacking interactions).1 has a repeating honeycomb-shaped internal structure with one-dimensional channels along the direction of the c axis, where the diameter of the aperture is as large as 18.83 Å. Furthermore, the stability and the optical band gaps are investigated.